Przesłanki i możliwości finansowania kapitałochłonnych inwestycji przez firmy telekomunikacyjne : studium przypadku - Buko, Jacek (The Premises and Possibilities of Financing of Capital - Intensive Investment by Telecommunication Firms : Case Study, 2005)
Activities of telecommunication firms in Poland concentrate round investment in infrastructure. The most frequent forms of obtaining moneys by firms are: bank-credit, leasing and issue of bond and stock. Limited size of financial supplies on national market induces firms to researches of money on international markets.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 98-105